Learning the spatiotemporal relationship between wind and significant wave height using deep learning. (15th February 2023) - Obakrim, Said; Monbet, Valérie; Raillard, Nicolas; Ailliot, Pierre
Abstract: Ocean wave climate has a significant impact on near-shore and off-shore human activities, and its characterization can help in the design of ocean structures such as wave energy converters and sea dikes. Therefore, engineers need long time series of ocean wave parameters. Numerical models are a valuable source of ocean wave data; however, they are computationally expensive. Consequently, statistical and data-driven approaches have gained increasing interest in recent decades. This work investigates the spatiotemporal relationship between North Atlantic wind and significant wave height ( H_s ) at an off-shore location in the Bay of Biscay, using a two-stage deep learning model. The first step uses convolutional neural networks to extract the spatial features that contribute to H_s . Then, long short-term memory is used to learn the long-term temporal dependencies between wind and waves.